Multiple imputation techniques: An application to Swiss value-added data - Jean-Marie Grether; Benjamin Tissot-Daguette (University of Neuchâtel, Institute of Economic Research (IRENE), 2021)
We use imputation techniques and combine official data sources to address the various shortcomings affecting the analysis of value-added data at the level of production units in Switzerland. The new ad hoc databases that emerge include consistent information on value added and employment at the level of geographically localized pseudo-firms over the 2011-2015 period. Our preferred sample is obtained through multiple imputation techniques, includes 18'000 pseudo-firms per year, covers two-third of Swiss municipalities and is suitable to address productivity issues at the microeconomic level.
Keywords: R11; R32; 330; Swiss firms; value-added; multiple imputation; spatial distribution